Hybridizing Triboelectric and Thermomagnetic Effects: A Novel Low‐Grade Thermal Energy Harvesting Technology. (13th February 2022) - Rodrigues, Cátia; Pires, Ana; Gonçalves, Isabel; Silva, Daniel; OIiveira, Joana; Pereira, André; Ventura, João
Abstract: Developing new energy generation technologies able to effectively convert low‐grade thermal energy into electricity is an urgent necessity to tackle the continuous surge in energy demand and mitigate climate change. Here, a hybrid device that couples triboelectric and thermomagnetic effects to generate electrical power in the presence of small temperature gradients near room temperature is demonstrated. The thermomagnetic effect allows to induce the periodic and sustained motion of a second‐order ferromagnetic material in temperature gradients below 30 °C. This mechanical motion is then converted into electrical energy using a low‐cost triboelectric nanogenerator (TENG). The applicability of this concept is demonstrated in a broad range of operating temperatures in both the cold (15 to 37 °C) and hot (60 to 90 °C) sides. It is further shown that the electrical power generated by the hybrid TENG is more than 35× higher than that obtained by a conventional thermomagnetic generator driven by magnetic induction. The obtained results show that this implementation is a feasible thermal energy conversion technology, further expanding the applicability of triboelectricity into the realm of room temperature thermal harvesting. Abstract : A self‐sustained energy harvesting device combining triboelectric and thermomagnetic effects is proposed to achieve the conversion of thermal energy into electricity and its working mechanism explains using thermal and electrostatic simulations. Compared with traditional devices driven by magnetic induction, the proposed hybridization leads to a power improvement of over 35×, thus providing a novel application field for triboelectric nanogenerators.